Gliding arc plasma jet for inhibiting mycotoxin production and apple brown rot by Alternaria alternata - Pereira, Viviane Lopes; Caramês, Elem Tamirys dos Santos; Almeida, Naara Aparecida; Chiappim, William [UNESP]; Pessoa, Rodrigo Sávio; Petraconi Filho, Gilberto; Rocha, Liliana de Oliveira (Elsevier, 2024)
The effect of gliding arc plasma jet (GAPJ) on Alternaria alternata was assessed using Potato Carrot Agar (PCAg) and Gala apples to investigate its potential for inhibiting brown rot disease caused by the fungus. Different treatment times (1, 3, 7, 10, and 15 min) of GAPJ were employed, and it was observed that treatments lasting 7, 10, and 15 min resulted in reduced mycelia growth, decreased fungal spore viability, and mitigated brown rot severity. Notably, the 15-min treatment demonstrated the highest efficacy in controlling A. alternata growth on PCAg and apple brown rot (p < 0.05). Additionally, it effectively reduced the number of viable spores and inhibited the production of A. alternata mycotoxins, including alternariol, alternariol monomethyl ether, and tenuazonic acid. The reactive species OH, NO, NO2 and NO3 are believed to be responsible for these effects, indicating that GAPJ holds potential for enhancing the safety of food products.
Keywords: Alternaria toxins; Non-thermal atmospheric pressure plasma; Secondary metabolites